2017
DOI: 10.2217/mmt-2016-0022
|View full text |Cite
|
Sign up to set email alerts
|

Skin Cancer Screening: Recommendations for Data-Driven Screening Guidelines and a review of the US Preventive Services Task Force Controversy

Abstract: Melanoma is usually apparent on the skin and readily detected by trained medical providers using a routine total body skin examination, yet this malignancy is responsible for the majority of skin cancer-related deaths. Currently, there is no national consensus on skin cancer screening in the USA, but dermatologists and primary care providers are routinely confronted with making the decision about when to recommend total body skin examinations and at what interval. The objectives of this paper are: to propose r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
84
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 60 publications
0
84
0
Order By: Relevance
“…For a user checking the skin lesions with this SA, it may prove difficult to evaluate all relevant skin lesions, as lay users may not know which lesions could be dangerous and/or which the user cannot see (namely for users taking an image without a partner and/or if the lesions are located in places which are hard to reach). On the other hand, this may also occur in current clinical practice as previous studies suggested GPs usually do not perform a full‐body skin examination …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a user checking the skin lesions with this SA, it may prove difficult to evaluate all relevant skin lesions, as lay users may not know which lesions could be dangerous and/or which the user cannot see (namely for users taking an image without a partner and/or if the lesions are located in places which are hard to reach). On the other hand, this may also occur in current clinical practice as previous studies suggested GPs usually do not perform a full‐body skin examination …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, this may also occur in current clinical practice as previous studies suggested GPs usually do not perform a full-body skin examination. 20,21 These risks are mitigated by the SA in several ways. First, every pair of image and corresponding risk rating gets a quality control by a dermatologist.…”
Section: Discussionmentioning
confidence: 99%
“…We thus advocate for skin self‐awareness and individuals should seek consultation with a medical professional for unusual spots or itching, bleeding, or changing moles. Finally, we support clinical evaluations with total body skin examinations for adults 35 to 75 years of age with personal history of skin cancer, family history of melanoma or hereditary predisposition to melanoma, light skin phototypes and red hair phenotypes, and/or a history of sun overexposure . Further evaluations and interval of follow up are dependent on the risk of the individual in consultation with a dermatologist.…”
Section: Discussionmentioning
confidence: 56%
“…Melanoma is the fifth most common invasive cancer in the USA, and its incidence is increasing around the world [27,28]. Melanomas are also responsible for the vast majority of skin cancer-related mortalities [28]. Skin cancer is screened visually with a total body skin examination.…”
Section: Melanomamentioning
confidence: 99%